2020
DOI: 10.3389/fonc.2019.01467
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Prostate Cancer Shows Similar Prognosis to Typical Prostate Acinar Carcinoma: A Large Population-Based and Propensity Score-Matched Study

Abstract: Background: Mucinous prostate cancer (PCa) is an extremely rare form of prostate malignancy. To date, the limited knowledge of its biology and outcomes stems from mostly small, single institution experiences. We analyzed the Surveillance, Epidemiology, and End Results (SEER) database to explore the incidence and treatment of mucinous PCa together with its prognostic factors to gain relatively large and consolidated insights. Methods: Age-adjusted incidence (AAI) rates were evaluated over time. Propensity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…of 73 cases mucinous PCa matched serum PSA, tumor volume, rate of extra-prostatic extension and 5-year biochemical recurrence rates, nally concluded similar prognosis between the two groups of tumors. Feng et al (12). found the same conclusion and indicated that patients did not receive radiation therapy had similar cancer-speci c mortality with radiation therapy patients, con rmed the experience that mucinous PCa showed poor response to radiotherapy reported by previous study (13).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…of 73 cases mucinous PCa matched serum PSA, tumor volume, rate of extra-prostatic extension and 5-year biochemical recurrence rates, nally concluded similar prognosis between the two groups of tumors. Feng et al (12). found the same conclusion and indicated that patients did not receive radiation therapy had similar cancer-speci c mortality with radiation therapy patients, con rmed the experience that mucinous PCa showed poor response to radiotherapy reported by previous study (13).…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, some studies showed that mucinous PCa didn't implicate poor prognosis than typical prostate acinar carcinoma (n = 60) (9). The latter were supported by several recent studies (2,(10)(11)(12). The study by Bronkema et al (10).…”
Section: Discussionmentioning
confidence: 93%
“…Prostate cancer (PCa) is one of the most prevalent urological cancers in men worldwide [1][2][3]. The incidence of PCa is increased worldwide in recent years [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence rate of this tumor is lower in Japan than that in Western countries (the incidence rates in Japan, the United States, and the United Kingdom are 27.0, 98.2, and 73.2 per 100,000 population, respectively) ( 5 ), its incidence is rapidly increasing with the westernization of lifestyles ( 6 ). Most malignant prostatic neoplasms (~90%) are adenocarcinomas ( 7 – 9 ). In patients who are required to undergo radical prostatectomy, various parameters can be evaluated through preoperative clinical investigations and histopathological analyses of surgical specimens.…”
Section: Introductionmentioning
confidence: 99%